1992
DOI: 10.1111/j.1532-5415.1992.tb04475.x
|View full text |Cite
|
Sign up to set email alerts
|

Community‐Acquired Bacteremia in the Elderly: A Prospective Study of 121 Cases

Abstract: Community-acquired bacteremia in the elderly has a high mortality rate. Early recognition and prompt, appropriate treatment are critical in reducing the mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
2
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 22 publications
2
25
2
1
Order By: Relevance
“…The elderly have an altered immune response and may fail to demonstrate traditional clinical indicators of infection (9 -12). The diagnosis of bacteremic UTI is often delayed in geriatric patients, resulting in reported mortality rates of 10% to 40% (11,(13)(14)(15). Despite risk for significant morbidity, the characteristics and outcome of elderly patients presenting to the ED with UTI have not been previously described in the literature.…”
Section: Introductionmentioning
confidence: 89%
“…The elderly have an altered immune response and may fail to demonstrate traditional clinical indicators of infection (9 -12). The diagnosis of bacteremic UTI is often delayed in geriatric patients, resulting in reported mortality rates of 10% to 40% (11,(13)(14)(15). Despite risk for significant morbidity, the characteristics and outcome of elderly patients presenting to the ED with UTI have not been previously described in the literature.…”
Section: Introductionmentioning
confidence: 89%
“…14 S. pneumonia, 22 and Enterobacteriaceaeresistantto3rdgenerationcephalosporins 14 werealso associatedwithincreasedmortality.E.coliwasdemonstratedto beprotectiveinonestudy. 48 InalargestudyfromFinland,thecase fatalityproportionsofGram-negativeBSIinpeople>D65ywas highercomparedtoyoungerpatientsandreached13%. 9 Another predictor of mortality is the use of inappropriate empiric antibiotic therapy 11,14,28,[46][47][48] and age is an important risk factor of carriage of multidrug resistant organisms leading possibly to higher rates of inappropriate empirical antibiotic treatment in elderly patients.…”
Section: Mortalitymentioning
confidence: 99%
“…9 Another predictor of mortality is the use of inappropriate empiric antibiotic therapy 11,14,28,[46][47][48] and age is an important risk factor of carriage of multidrug resistant organisms leading possibly to higher rates of inappropriate empirical antibiotic treatment in elderly patients. 6 Clinical signs at presentation predicting mortality among the elderly include hypotension/ shock, 11,13,14,46,48,61 absence of fever, 14,22 low albumin, 11,41,61 elevated renal creatinine/ urea, 11,13,61 leukopenia, 22,61 change in mental status, 29,48 and in single studies other measures such as tachycardia or tachypnea, 61 elevated CRP 41 and early organ failure. 22 …”
Section: Mortalitymentioning
confidence: 99%
“…Previous studies have investigated bacteremia in older patients, and UTI was found to be the source of bacteremia in 24-56% of the patients [2,19]. In patients with community-acquired bacteremia, 30-40% of the patients had UTI [20][21][22]. In older adults with bacteremic UTI, 80.1-83.3% of the infections were community-acquired [5,23].…”
Section: Discussionmentioning
confidence: 91%